BLACK HOLE Attack: A New Detection Technique - Kumar, Vipul; Vaqar, Musheer (International Journal of Computer Sciences and Engineering, 2025)
Due to the wireless nature and infrastructure-less environment of WSN, they are more vulnerable to many types of security attacks. This paper proposes a technique to detect the black-hole attack using multiple base-stations and a check agent based technology. This technique is Energy efficient, Fast, Lightweight and Reduces message complexity. An effective solution is proposed that uses multiple base stations to improve the delivery of the packets from the sensor nodes reaching at least one base station in the network, thus ensuring high packet delivery success. The proposed technique is more efficient than the previous techniques and gives better results. Check agent is a software program which is self-controlling and monitoring, smart homes, structures, target it moves from node to node and checks wireless nodes envelop embedded electronic sensors along with battery and RF devices. The purpose of these sensors is to sense and recognize diverse biological parameters, for instance, temperature, pressure, air pollution etc., to communicate with the neighboring nodes and compute the gathered data. Their application space is huge as they can be deployed in various fields like agriculture the presence tracking, health care, and military surveillance and of black-hole nodes in the network. Routing through multiple base stations algorithm is only activated when there is a chance of black-hole attack on the network. This method prevents the black hole attack imposed by both single and multiple black hole nodes. The tool used to implement the proposed algorithm is NS2, which is an object oriented event drive software package. The result of the simulation study expected to get good network performance by minimizing the packet losses as well as effectively prevent the black hole attack against wireless sensor networks. A solution to avoid the black hole attack has been proposed. The solution will be implemented in NS-2.